Suspected Transient Ischemic Attack Related to Dysfunctional Quadricuspid Aortic Valve - Arun Katwaroo MBBS; Jessica Kawall MBBS; Priya Ramcharan MBBS; Valmiki Seecheran MBBS, MSc; Rajeev Seecheran MBBS, MHA; Nafeesah Ali MBBS; Shari Khan MBBS; Naveen Anand Seecheran MBBS, MD, MSc (Journal of Investigative Medicine High Impact Case Reports)
We describe a 30-year-old Caribbean-Black woman with a clinical presentation suggestive of a transient ischemic attack (TIA) with no conventional cerebrovascular risk factors, albeit with a newly diagnosed quadricuspid aortic valve (QAV) with moderate aortic regurgitation (AR). Although QAV is a recognized congenital cardiac defect, its association with TIA remains elusive. This case highlights the importance of considering potential atypical etiologies, such as QAV, in the evaluation and management of young patients presenting with cerebrovascular events.